Brain-eating amoebae: Predilection sites in the brain and disease outcome - Ong, Timothy Yu Yee *; Khan, Naveed Ahmed *; Siddiqui, Ruqaiyyah Bano * (American Society for Microbiology, 2017)
Acanthamoeba spp. and Balamuthia mandrillaris are causative agents of granulomatous amoebic encephalitis (GAE), while Naegleria fowleri causes primary amoebic meningoencephalitis (PAM). PAM is an acute infection lasting few days, while GAE is a chronic to subacute infection that can last up to several months. Here, we present a literature review of 86 case reports from 1968 to 2016 in order to explore affinity of these amoebae towards particular sites of the brain, diagnostic modalities, treatment options and the disease outcome in a comparative manner.